2006
DOI: 10.1074/jbc.m510504200
|View full text |Cite
|
Sign up to set email alerts
|

Sequence, Distance, and Accessibility Are Determinants of 5′-End-directed Cleavages by Retroviral RNases H

Abstract: The RNase H activity of reverse transcriptase is essential for retroviral replication. RNA 5-end-directed cleavages represent a form of RNase H activity that is carried out on RNA/DNA hybrids that contain a recessed RNA 5-end. Previously, the distance from the RNA 5-end has been considered the primary determinant for the location of these cleavages. Employing model hybrid substrates and the HIV-1 and Moloney murine leukemia virus reverse transcriptases, we demonstrate that cleavage sites correlate with specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 55 publications
3
44
0
Order By: Relevance
“…Here, with recombination forced to occur principally from a single-template position, 16 bases of identity were sufficient to target accurate and efficient recombinogenic switching. Similar trends in acceptor recognition have previously been reported using different sequences and more-limited sets of length variation, suggesting that whereas some interactions between RT and nucleic acids differ by sequence, the observations here are not specific to the target sequences used (10,43,52). …”
Section: Discussionsupporting
confidence: 67%
“…Here, with recombination forced to occur principally from a single-template position, 16 bases of identity were sufficient to target accurate and efficient recombinogenic switching. Similar trends in acceptor recognition have previously been reported using different sequences and more-limited sets of length variation, suggesting that whereas some interactions between RT and nucleic acids differ by sequence, the observations here are not specific to the target sequences used (10,43,52). …”
Section: Discussionsupporting
confidence: 67%
“…The third determinant is the accessibility of the end. Thus, while the 5′ end at a nick is not recognized by reverse transcriptase for RNA 5′ end-directed cleavages, a gap of 2 or more bases is sufficient for such recognition and cleavage by the HIV-1 and MoMLV enzymes (Schultz et al, 2004;Schultz et al, 2006).…”
Section: Rna 5′ End-directed Cleavagementioning
confidence: 99%
“…Similar to DNA 3′ end-directed cleavages, two of these determinants are distance from the recessed end (DeStefano et al, 1993), and the nucleotide sequence in the vicinity of the cleavage site [see section 6.1; (Furfine and Reardon, 1991b;Fu and Taylor, 1992;DeStefano et al, 1993;Schultz et al, 2006)]. The third determinant is the accessibility of the end.…”
Section: Rna 5′ End-directed Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…Rausch and Le Grice also did in vitro assays with mutant PPTs with A substitutions in the G tract of the HIV-1 PPT and showed that the A1, A2, A3, and A5 mutations affected the specificity or extent of cleavage (22). Schultz et al reported, based on in vitro cleavage of non-PPT sequences, that the RNase H of HIV-1 RT cleaves poorly if the substrate has the equivalent of an A3, T5, or A5 substitution (29).…”
mentioning
confidence: 99%